The intelligent tidal volume control - Güler, Hasan; Ata, Fikret (My University, 2010)
In this study, closed loop fuzzy control of tidal volume parameter which is controlled in mechanical ventilators used at intensive care units (ICU) and veterinary faculties for experimental studies was implemented. Because of the fact that clinicians may not be in vicinity of the patients, tidal volume which is one of the most followed parameters for patients was controlled with closed loop fuzzy controller.Thus, it is aimed to decrease the work load of clinicians. Two seperate studies were implemened and their performances were compared. The input parameters of fuzzy system are heart rate(HR), blood pressure(BP), peak pressure (PP) and SaO2(Oxygen saturation). Performed system is run with the pressure support ventilation (PSV) which is one of the most used modes among other ventilation modes.
Akilli tidal volüm kontrolü
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- 2 December 2010 through 5 December 2010 -- Bursa -- 83834
Keywords: Blood pressure; Electrical engineering; Fuzzy control; Fuzzy logic; Fuzzy sets; Oxygen; Closed loops; Experimental studies; Heart rates; Input parameter; Oxygen saturation; Peak pressure; Pressure support ventilation; Tidal volume; Ventilation mode; Work loads; Intensive care units